Mathematical modelling of covid-19 using health mask, vaccination, quarantine, and asymptomatic case - Manaqib, Muhammad; Wijaya, Madona Yunita; Yahya, Amelia Nur (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study develops a SEIR (Susceptible, Exposed, Infectious, and Recovered) model to model the spread of COVID-19 by adding the use of health masks, vaccinations, quarantines, and asymptomatic compartments. The model is analyzed using equilibrium point stability analysis and numerical simulation. Based on the system, two equilibrium points are obtained, namely the disease-free equilibrium point and the endemic equilibrium point, and the basic reproduction number (Ro). The stability analysis of the disease-free equilibrium point will be locally asymptotically stable if Ro<1. The numerical simulation results show that the disease will disappear from the population if Ro<1 and remain in the population if Ro>1 . Based on the sensitivity analysis, parameters with significant impact are the level of awareness of individuals in using health masks, vaccination rates, contact rates with symptomatic or asymptomatic infected individuals, and quarantine rates for symptomatic infected individuals.